Symbolism of the Monogram Om - Pandiyappillil, Joseph (Journal of Dharma, 1984)
Many symbols are used in Hinduism among which 0M is the most important one. 0M is a word of invocation, affirmation, benedication and consent. 1 Regarding its meaning there are various opinions and the most widely supported view is that the word is an exclamation. 2 Hence the highest mantra 0M, does not convey any particular name of Divinity, nor recall any mythological or semihistorical event but is an inarticulate exclamation when man is confronted with the presence in himself and around himself. 3 This syllable of mystical power was considered to be sacred and therefore the sudras and the other lower class of people were not allowed to utter it; but were allowed to derive some satisfaction by uttering aun. 4 0M symbolizes the Reality which is the fulness and the mystery of mysteries by the meditation of which one can attain divine realization.